PENINGKATAN HASIL BELAJAR SISWA BERKEBUTUHAN KHUSUS SMPN 4 MATARAM DALAM MEMAINKAN ALAT MUSIK RECORDER MENGGUNAKAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING LEARNING (CTL) - ENDANG SRININGSIH (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2023)
In the millennium era, formal and non-formal education is growing rapidly. Non-formal education can support formal education, both have positive impacts. In formal education from elementary school/equivalent to high school/equivalent there is arts education. Art education is needed to balance the right brain with the left brain. Educating students to become people who appreciate works of art according to local characteristics and making them students who enjoy reading and writing works of art is not easy. In general, students like Arts and Culture lessons. However, in reality only a few students can do art. If students are asked to move forward one by one, their playing technique is not good, they tend to be embarrassed, don't want to, and some say they can't. The teacher's efforts to overcome the above problem require quite serious time and attention, this is because the level of musicality of each student is different even though they both have a feeling of enjoyment in the Music Arts lesson. To motivate students to improve their musicality and understanding of music theory, the method used is: finding and practicing the easiest way to learn, practicing repeatedly from the easiest to the most difficult notes using the Contextual Teaching Learning (CTL) learning model. The aim of this learning innovation is to determine the learning outcomes of students with special needs in class IX 2 Odd Semester 2018/2019 Academic Year in the Arts and Culture (Music Arts) subject, especially regarding the easiest way to play recorder musical instruments using the CTL learning model. The results of this learning innovation show that the CTL learning model can improve the ability of students with special needs and regular needs in playing songs using recorder musical instruments. This can be seen from the results of written tests and practical tests. ABSTRAKDi era milenium, pendidikan formal dan nonformal semakin berkembang pesat. Pendidikan nonformal dapat menunjang pendidikan formal, keduanya berimbas positif. Dalam pendidikan formal dari tingkat SD/ sederajat hingga SMA/ sederajat terdapat pendidikan kesenian. Pendidikan Seni dibutuhkan untuk menyeimbangkan otak kanan dengan otak kiri. Mendidik para siswa agar menjadi insan yang menghargai karya seni sesuai dengan kekhasan lokal dan menjadikan mereka sebagai siswa yang gemar membaca dan menulis karya seni tidaklah mudah. Secara umum, para siswa menyukai pelajaran Seni Budaya. Namun dalam kenyataannya hanya sedikit siswa yang bisa berkesenian. Apabila para siswa disuruh maju satu persatu teknik permainannya kurang bagus, cenderung malu, tidak mau, dan sebagian lagi mengatakan tidak bisa. Usaha guru untuk mengatasi hal tersebut di atas membutuhkan waktu dan perhatian yang cukup serius, hal ini disebabkan oleh tingkat musikalitas setiap siswa berbeda meskipun sama-sama mempunyai rasa senang terhadap pelajaran Seni Musik. Untuk memotivasi siswa dalam meningkatkan musikalitas dan pemahaman terhadap teori musik, cara yang ditempuh: mencari dan mempraktikkan cara termudah dalam belajar, latihan berulang-ulang dari nada-nada yang termudah hingga yang tersulit dengan menggunakan model pembelajaran Contextual Teaching Learning (CTL). Tujuan inovasi pembelajaran ini untuk mengetahui hasil belajar siswa berkebutuhan khusus yang terdapat di kelas IX 2 Semester Ganjil Tahun Ajaran 2018/ 2019 pada mata pelajaran Seni Budaya (Seni Musik) khususnya terkait cara termudah bermain alat musik recorder dengan menggunakan model pembelajaran CTL. Hasil inovasi pembelajaran ini menunjukkan bahwa model Pembelajaran CTL dapat meningkatkan kemampuan siswa berkebutuhan khusus dan regular dalam memainkan lagu dengan menggunakan alat musik recorder. Hal ini dapat dilihat dari hasil tes tertulis dan tes praktek.